Efficacy of motivational enhancement therapy to decrease alcohol and illicit-drug use in pregnant substance users reporting baseline alcohol use - Osterman, Robin (J Subst Abuse Treat, 2017)
BACKGROUND: Approximately 35% of pregnant substance users in treatment report alcohol abuse, which increases the risk of fetal alcohol spectrum disorders (FASD) in their offspring. The present study was a preliminary evaluation of the efficacy of motivational enhancement therapy (MET) in decreasing alcohol use in pregnant women attending substance use treatment. METHODS: Secondary analysis of a trial evaluating the efficacy of MET, relative to treatment as usual (TAU), in improving treatment outcomes in 200 pregnant substance users. The present study included the 41 women (n=27 MET and n=14 TAU) who reported alcohol use in the 28 days prior to randomization. Alcohol and illicit-drug use days were assessed with self-report; illicit drug use was assessed with urine drug screens. All measures were obtained weekly for the 4 week active study phase and at 1 and 3 month follow-ups. RESULTS: Significant treatment-by-time interaction effects were found for illicit-drug use days during the active (X(2) = 6.89, df = 1, p < .01) and follow-up (X(2) = 8.26, df = 1, p < .01) phases and for alcohol use during the follow-up phase (X(2) = 13.07, df = 1, p < .001), all reflecting a beneficial effect for MET, relative to TAU. All other treatment effects were non-significant. CONCLUSIONS: These findings suggest that MET may be effective in decreasing alcohol and illicit-drug use in pregnant substance users reporting alcohol use. With 2–5% of US births affected by FASD, future research to replicate these findings seems warranted.